Incidental extraction and reimplantation of the urinary bladder in a canine with pyometra at the Veterinary Medical Hospital ASMEVET. Case report - Chávez, Luis E. (2021)
This report presents and documents a surgical complication in a 4-year-old Beagle dog, whose bladder was sectioned at the neck level during an exploratory celiotomy performed to correct a stump pyometra originated at the time of a selective ovariohysterectomy. The patient was referred to the ASMEVET Veterinary Medical Hospital in the city of Tunja, Boyacá, Colombia, with a history of vomiting, depression and dysuria days after the surgical procedure. Physical examination revealed increased rectal temperature, prostration, and pain on palpation of the abdomen. Samples were taken for a blood count and blood chemistry to evaluate kidney and liver function. In addition, an abdominal ultrasound was performed. Differential diagnoses were iatrogenic ureter obstruction, cervical pyometra, foreign body peritonitis, and paralytic ileus. A celiotomy was performed where an abscess and sequestration of the surrounding viscera were evidenced. In the attempt to separate them, the bladder was sectioned at the level of the neck. This was reimplanted with a Gambee suture pattern and supplemented with omentalization. The patient regained urination control.